Pasture cropping and keyline plow as strategies to mitigate compaction in clay soils in Vermont - Berdakh Utemuratov; Juan P. Alvez; Paliza Shrestha; Joshua W. Faulkner (Agricultural & Environmental Letters, 2025)
Abstract Field plot experiments were conducted over 3 years at two farm sites in Vermont to evaluate the effects of mechanical subsoiling and three pasture cropping mixes on soil compaction across rotationally grazed pasturelands with contrasting management histories in Vermont. Penetration resistance was measured across the 0–45.7 cm profile using both profile‐level and depth‐stratified analyses. Among the biological treatments, the sudangrass‐based mix achieved the greatest compaction alleviation, particularly at the site with higher initial severity. At the northern site (Health Hero [HH] Farm), this mix produced significantly lower median penetration resistance (1.59 MPa) and a narrower interquartile range (0.93 MPa) than other treatments, indicating more uniform soil improvement. At the southern site (Philo Ridge [PR] Farm), keyline plowing resulted in the lowest median resistance (1.41 MPa) but showed greater variability across replicates. Depth‐wise trends revealed that biological mixes, particularly the sudangrass‐based mix, provided consistent alleviation across soil layers. These findings highlight the value of biologically tailored strategies not only for reducing compaction but also for achieving spatially uniform soil structure recovery. Tailoring species composition to compaction depth offers a practical and lower disturbance alternative to mechanical tillage for improving pasture systems.